Hubungan antara ilmu, dan teknologi, budaya, peradaban - Silfiana, Tina (Maliki Interdisciplinary Journal, 2024)
The development of the use of science and technology is very rapid, this is an effort to improve the quality of education and technology to ensure the progress of the next generation. Science and technology continue to be fundamental to human life. Science as a product of the human mind is a culture. science can also be considered the last product of human mental development and is considered the best product of human culture. The objects studied are science, technology, culture and civilization. The type of research used is library research with non-numerical data presentation. The pattern of human needs continues to develop so that adjustments occur for the practicality of human life so that science and technology have continuity in supporting human life. The mind and hands collaborate to produce a culture so that progress occurs into a physical and spiritual civilization which is included in the aspect of intelligence that supports the progress of the nation. There is a relationship between science and technology and culture and civilization. The development of science and technology continues to produce new discoveries that affect culture so as to bring a nation to the progress of human civilization.